Fundamentals of Social Identity and Social Justice: Considering Social Identity Within CBPR With Marginalized Populations - Huse, Laura-Kate (Frontiers in Communication, 2020)
Community-based participatory research (CBPR) is a research paradigm that works with marginalized populations within health contexts. The partnership between scholars and marginalized populations empowers participants through the pursuit of social justice. However, there has been a cry for standardizing the CBPR approach particularly when working with marginalized populations. Identity is a critical construct to understand within the communities in order to collectively strive towards social justice. This paper examines how social identity theory can aid community-based participatory research teams by a) illustrating how social identity analysis can facilitate the researcher-community partnership, b) applying SIT to better understand community behaviors and norms, and c) using SIT to avoid unintended consequences within CBPR intervention designs. Through understanding identity, relational empowerment can be positively redistributed back to community members. This paper will thus serve as a first step in justifying why more research is needed in incorporating social identity to CBPR intervention designs.